2019
DOI: 10.1186/s12872-019-1110-7
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-lymphocyte and platelet-to-lymphocyte ratio in Chinese Han population from Chaoshan region in South China

Abstract: Background Neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) are assumed to be prognostic factors in many diseases such as inflammatory diseases, cardiovascular diseases and cancer. However, NLR and PLR are race specific, it is important to determine the reference values of NLR and PLR in different races. The study aimed to investigate the reference range of NLR and PLR in Chinese Han population from Chaoshan region in South China. Methods A re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 30 publications
2
53
1
3
Order By: Relevance
“…This might be due to an insufficient sample size of patients with high creatinine level (n = 57 in our study), although we had a relatively large overall sample. In addition, previous study pointed out that the value of PLR varied with age and sex [34], we therefore performed a subgroup analysis to verify whether the predictive value of PLR was consistent among different populations. The subgroup analysis also confirmed that the relationship between PLR and mortality remained stable across all the age groups, as well as male or female subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…This might be due to an insufficient sample size of patients with high creatinine level (n = 57 in our study), although we had a relatively large overall sample. In addition, previous study pointed out that the value of PLR varied with age and sex [34], we therefore performed a subgroup analysis to verify whether the predictive value of PLR was consistent among different populations. The subgroup analysis also confirmed that the relationship between PLR and mortality remained stable across all the age groups, as well as male or female subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…41 Although PLR has been shown to be associated with prognosis of lung cancer in previous studies, studies on a predictive role of PLR in development of lung cancer are currently limited. [29][30][31][32] Previous studies reported a sex difference in PLR, with higher PLR in women than in men, 42,43 but studies address sex differences in the relationship between PLR and lung cancer risk are scarce. Although the mechanisms of sex-related differences in PLR are not fully understood, several factors, such as estrogen and low iron saturation in menstruating women, may affect platelet counts.…”
Section: Discussionmentioning
confidence: 99%
“…Platelet to lymphocyte ratio (PLR) is an indicator of prognosis in cardiovascular diseases, rheumatic disorders, infectious diseases, and organ injuring disorders such as systemic erythematous lupus (SLE) and malignancies [ 10 , 12 ] Platelets have dual properties involving both hemostasis and immunity [ 13 , 14 ]. This ratio is easily accessible and is calibrated by a complete blood count (CBC) test [ 15 ]. The platelet to lymphocyte ratio is also dependent upon age and gender, with women detected with elevated PLR at the age of 30–59 and decreased levels at the age of 50 as compared to males [ 15 ].…”
Section: Introductionmentioning
confidence: 99%